Pengaruh Analisis Kredit Terhadap Pembiayaan Bermasalah (Kredit Macet) Pada PT. Bank Pembiayaan Rakyat Syariah Artha Madani Cikarang, Jawa Barat - Tavitri Rangkuti (Institut Ilmu Sosial dan Manajemen STIAMI, 2018)
Credit is a risky business, where there is a possibility of credit being given uncollectible (bad credit). Debtors (credit recipients) can present a million reasons for not paying their obligations. On the other hand the bank must pay every rupiah of public funds placed on it. The bank can not say that the loans it provides are not collectible, the public funds can not be paid. In this regard, banks should only provide financing (credit) to the appropriate debtor. The bank must be able to control the credit risk it provides. The Bank developed a selection process to screen each proposed credit (proposed financing) proposal. In giving credit, the bank must have the trust to the prospective debtor as well as the debtor has the confidence to save the funds in the bank. Funds provided will be used in accordance with the objectives and will eventually be returned to the bank in accordance with the agreed agreement. This credit grant has a high enough risk factor and has a significant effect on Bank soundness. Therefore, PT BPRS (Islamic Loan Bank) Artha Madani analyzes credit well before approving financing for prospective borrowers and gives attention to various aspects related to financing processing.This type of research is associative. Data Collection Technique is done by Library Study and Field Study. Sampling technique is based on the provisions of percentage according to Suharsini Arikunto (1993: 120). Total population The number of employees of PT BPRS Artha Madani is 53 people, so the sample is taken as many as 15 people. Data Analysis Technique is calculated by using the average value of Likert scale, correlation coefficient and determination.From the results of research, it is found that the magnitude of responses of respondents to variable credit analysis indicates a number of 4.01 which means credit analysis on PT BPRS Artha Madani has been running well. The coefficient r obtained is 0.728 and this value shows the relationship of variable x (credit analysis) with variable y (financing approval) is strong.